2007
DOI: 10.1016/j.mrgentox.2007.03.002
|View full text |Cite
|
Sign up to set email alerts
|

In vitro micronucleus assay scored by flow cytometry provides a comprehensive evaluation of cytogenetic damage and cytotoxicity

Abstract: This laboratory has previously reported on the development of a flow cytometry-based method for scoring in vitro micronuclei in mouse lymphoma (L5178Y) cells [Avlasevich et al., Environ. Molec. Mutagen. 47 (2006) 56-66]. With this method, necrotic and mid/late stage apoptotic cells are labeled with the fluorescent dye ethidium monoazide. Cells are then washed, stripped of their cytoplasmic membranes, and incubated with RNase plus a pan-nucleic acid dye (SYTOX Green). This process provides a suspension of free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
165
1
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 176 publications
(176 citation statements)
references
References 43 publications
4
165
1
6
Order By: Relevance
“…The high numbers of cells captured by the ISX illustrate the improvement in statistical robustness that can be achieved in comparison to microscope‐based versions of the assay. In addition, conventional flow cytometry methods that do not use Cyt‐B typically analyze between 20,000 and 40,000 lysed nuclei 30, 31, 61. The number of MONO cells scored from samples treated without Cyt‐B using the ISX method fall roughly in the middle of this range and have the added benefit of associated BF and fluorescent imagery for every cell collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high numbers of cells captured by the ISX illustrate the improvement in statistical robustness that can be achieved in comparison to microscope‐based versions of the assay. In addition, conventional flow cytometry methods that do not use Cyt‐B typically analyze between 20,000 and 40,000 lysed nuclei 30, 31, 61. The number of MONO cells scored from samples treated without Cyt‐B using the ISX method fall roughly in the middle of this range and have the added benefit of associated BF and fluorescent imagery for every cell collected.…”
Section: Discussionmentioning
confidence: 99%
“…The speed of this method and the need for minimal user intervention are attractive features for toxicology testing. Over the last decade, significant improvements were made to the methodology by Avlasevich et al 30 and Bryce et al 31 to incorporate additional fluorescent dyes in order to remedy the difficulties encountered when differentiating MN, cellular debris, and free chromosomes from mitotic cells. This method was successful and configured into a commercially available kit by Litron Laboratories and several publications employing many well‐known clastogens and aneugens have demonstrated that statistically significant increases in MN frequency can be detected when compared with controls 32, 33.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent stripping of cytoplasmic membranes and incubation with the pan-nucleic acid dye SYTOX Green (plus RNase) provides a suspension of free nuclei and micronuclei (MN) that are differentially stained relative to chromatin associated with dead/dying cells. Using this method, good agreement between microscopy-and flow cytometry-based scoring was reported for mouse L5178Y and human TK6 cells [12][13].…”
Section: Introductionmentioning
confidence: 87%
“…Importantly, the measurement is a multi-parametric assessment of cell health, as it requires nuclei to be EMA-negative, and also to exhibit forward and side scatter characteristics of healthy nuclei. Based on our previous work with this endpoint [13], we hypothesize that the Flow-NBR will tend to be a more sensitive indicator of cytotoxicity than most widely utilized methods. Experiments described herein included several additional cytotoxicity assays that served as a basis for evaluating the reliability and sensitivity of the Flow-NBR endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Further modifications use a 96‐well format in conjunction with a robotic auto‐sampling device. This adaptation requires less test material than conventional test methods, and has a greater compatibility with HTS instrumentation 138, 139, 140, 141…”
Section: High‐throughput In Vitro Micronucleus Assaymentioning
confidence: 99%